PENANGGULANGAN KORUPSI MELALUI PENDEKATAN TEOLOGIS BERBASIS AL-QURAN - Muhammad Suaib Tahir; Ali Fikri Noor (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2020)
This study concludes that overcoming corruption with a non-theological conventional approach is deadlocked, which is caused by a moral crisis, identity, and social situation, and group propaganda that prioritizes corruption prevention strategies with an approach to improving legislation rather than theological approach. The conventional, non-theological approach has so far turned out to be ineffective, because it is only superficial (saṭḥiyyun wa ẓāhiriyyun), not a deep solution, that is, a solution that reaches deep into the substance of the problem, namely theological or religious approach. The perspective of the Qur'an in dealing with corruption is found through three strategies, namely: detective, preventive, and repressive. Detective and preventive strategies are pursued in three ways: strengthening faith, strengthening the heart, and strengthening morality. Meanwhile, the repressive strategy is pursued in four ways: strengthening supervisory institutions (al-ḥisbah), strengthening juridical law and the judiciary, strengthening communities, and strengthening aspects of religiosity. Meanwhile, the detective, preventive, and repressive strategies as a whole are taken through strengthening theological values. The method used in this study is a qualitative method, based on library research, verses of the Qur'an, publications in the form of research results, journals, seminars, and articles. While the interpretation method used is the thematic interpretation method (tafsīr mawḍū’ī), both when analyzing problems from a theological point of view and when using verses of the Qur'an.